Delayed Cerebral Infarction is Systematically Associated with a Cerebral Vasospasm of Large Intracranial Arteries. Issue 2 (9th September 2019) - Brami, Jonathan; Chousterman, Benjamin; Boulouis, Grégoire; Dorze, Matthieu Le; Majlath, Melinda; Saint-Maurice, Jean-Pierre; Civelli, Vittorio; Froelich, Sébastien; Houdart, Emmanuel; Labeyrie, Marc-Antoine
Abstract: BACKGROUND: Whether delayed cerebral infarction (DCIn) after aneurysmal subarachnoid hemorrhage (aSAH) is driven by large artery vasospasm is still controversial. OBJECTIVE: To study the association between DCIn and vasospasm by using quantitative assessment of vasospasm up to distal arteries with time and territorial-based correlation. METHODS: Clinical and imaging data of 392 patients with aSAH treated at our center between 2012 and 2017 were reviewed. DCIn was defined as any cerebral infarction occurring within 3 to 21 d after ictus and not related to other specific cause. In patients with DCIn, vasospasm was assessed within 24 h around DCIn for each cerebral artery up to the end of the 2nd segments. DCIn and vasospasm analyses were blinded. RESULTS: DCIn was found in 11% of patients (inter-rater k = 0.90, computed tomography (CT)-scan = 100%, follow-up MRI = 91%). Vasospasm was quantified in 258 artery territories including 66 with and 192 without DCIn (DSA = 93%, computed tomography angiography = 7%). Vasospasm was more severe in DCIn than in non-DCIn territories (60% [55-69] vs 20% [0-50], P < .001). Vasospasm was associated with DCIn in a "dose-dependent" manner ( P for trend = .022). Every DCIn territory had a vasospasm ≥ 50%, including 39% only of distal artery segments. Only 9% of non-DCIn territories had vasospasm ≥ vasospasm in DCIn territories. CONCLUSION: The necessary association between severe vasospasm and DCIn in our study brings additional arguments in favor of large artery vasospasm (especially of distal segments) as a major determinant of DCIn and a potential therapeutic target.